Learning Islam from the Performance of Wayang Kulit (Shadow Puppets) - Ferdi Arifin (Hunafa: Jurnal Studia Islamika, 2017)
Shadow puppet is the oldest heritage culture in Indonesia. There are many local wisdom values embedded in shadow puppet, so it can be a reason of the existence of shadow puppet throughout the ages. One of facts shows us that shadow puppet is well-knows as the greatest heritage for a history of spreading Islam used to a shadow puppet media by Sunan Kalijaga. This research employs qualitative method which direct observes this performing arts to find facts that shows shadow puppet is being regarded as dawa media. In fact, shadow puppet has essential role for spreading Islam in Indonesia because it has a linier values with Islam itself. The result explains us that language facts derives from wejangan form in shadow puppet representing Islamic values. Therefore, shadow puppet can be a Islamic learning media for all people.